Reproducibility and relative validity of a semi-quantitative food frequency questionnaire for Chinese pregnant women - Zhang, Hongmin (Nutr J, 2015)
BACKGROUND: Food frequency questionnaire (FFQ) is a reliable tool to estimate dietary intake in large nutritional epidemiological studies, but there is lack of a current and validated FFQ for use in urban Chinese pregnant women. This study aimed to evaluate the reproducibility and validity of a semi-quantitative FFQ designed to estimate dietary intake among urban pregnant women in a cohort study conducted in central China. METHODS: In the reproducibility study, a sample of 123 healthy pregnant women completed the first FFQ at 12–13 weeks gestation and the second FFQ 3–4 weeks later. To validate the FFQ, the pregnant women completed three 24-h recalls (24HRs) between the intervals of two FFQs. RESULTS: The intraclass correlation coefficients of two administrations of FFQ for foods ranged from 0.23 (nuts) to 0.49 (fruits) and for nutrients from 0.24 (iodine) to 0.58 (selenium) and coefficients were all statistically significant. The unadjusted Pearson correlation coefficients between two methods ranged from 0.28 (beans) to 0.53 (fruits) for foods and from 0.15 (iodine) to 0.59 (protein) for nutrients. Energy-adjusted and de-attenuated correlation coefficients for foods ranged from 0.35 (beans) to 0.56 (fruits) and for nutrients from 0.11 (iodine) to 0.63 (protein), and all correlations being statistically significant except for iodine, sodium and riboflavin. On average, 67.0 % (51.2 %-80.5 %) of women were classified by both methods into the same or adjacent quintiles based on their food intakes, while 68.5 % (56.1 %-77.2 %) of women were classified as such based on nutrient intakes. Extreme misclassifications were very low for both foods (average of 2.0 %) and nutrients (average of 2.2 %). Bland-Altman Plots also showed reasonably acceptable agreement between two methods. CONCLUSION: This FFQ is a reasonably reliable and valid tool for assessing most food and nutrient intakes of urban pregnant women in central China.